Variation in Growth, Wood Density, and Stem Taper Along the Stem in Self-Thinning Stands of Sassafras tzumu - Diao, Songfeng; Sun, Honggang; Forrester, David I.; Soares, Alvaro A. V.; Protásio, Thiago P.; Jiang, Jingmin (Frontiers in Plant Science, 2022)
Silvicultural practices greatly improve the economic value of wood products from forests. Stem dimensions, wood density, and stem form are closely linked to end-product performance. This research aimed to examine the effects of stand density and stem height on variables that reflect ring growth and wood properties of Sassafras tzumu stands during the self-thinning phase. Between the ages of 10 and 40 years, the number of stems per hectare has declined from 1,068 to 964 due to density-dependent mortality. As the relative stand density decreased, there were significant reductions in the average tree ring width (5.07–3.51 mm) and increases in latewood proportions (49.88–53.49%) and the density of the annual growth ring (165.60–708.58 kg/m3). Therefore, ring density, earlywood density, and latewood density increased with decreasing relative stand density after self-thinning occurred. Ring width, earlywood width, and latewood width significantly increased from the base to the apex of the stem. Stand density and stem height had additive effects on S. tzumu wood properties during the self-thinning phase. A shift in the growth allocation along the longitudinal stem in response to self-thinning resulted in decreasing radial growth, increasing wood density, and improved stem form. In summary, we found a significant influence of stand density on tree ring growth, wood quality, and stem form of S. tzumu trees during the self-thinning phase.